An Investigation into the Challenges Facing Collection and Distribution of Educational Data in F.C.T Educational Institutions, Abuja, Nigeria - Ogunode Niyi Jacob; Adah Samuel; Auduh Elizabeth I; Abubakar Musa (Garuda Prestasi Nusantara Consulting, 2021)
This study investigated the challenges facing the collection and distribution of educational data in F.C.T Educational institutions, Abuja, Nigeria. The researchers used descriptive research survey design for the study. The study comprised a population of one hundred and twenty (120) respondents which made up of data collection officers in the selected educational institutions across the FCT. Ten (10) data collection officers from each area council and ten (10) data collection officers from six departments/agencies/units within the ministries of education in Abuja were used in the study. Purposive, Stratified and systematic sampling technique was used to select the sample population from the educational institutions across Abuja. The reliability of the instrument was determined through the test re-test method. Data was collected by questionnaire and were analyzed using percentage and chi-square. The study led to the conclusion that inadequate funding, shortage of professional data collection officers, inadequate working materials, institutional corruption, poor capacity development programme of data collection officers, poor methods and approaches used for collecting data, poor supervision and inspection and political influence are the problems hindering effective data collection and distribution in educational institutions. The study also established that there is significant relationship between challenges and collection and distribution of educational data in schools. Based on this finding, the following were recommended: that the federal, state and local government should increase the funding of education and more priority should be given to data collection and distribution funding and the government at every level in FCT should employ more data collection officers and deploy them to the primary and secondary schools in FCT.